Theoretical and Experimental Study of the Vibration Dynamics of a 3D-Printed Sandwich Beam With an Hourglass Lattice Truss Core - Guo, Zhenkun; Hu, Guobiao; Jiang, Jingchao; Yu, Liuding; Li, Xin; Liang, Junrui (Frontiers in Mechanical Engineering, 2021)
3D printing (also known as additive manufacturing) has been developed for more than thirty years. The applications of 3D printing have been increasingly extended to a variety of engineering fields in recent years. The sandwich material with high strength and overall low density is a kind of artificial material that has been extensively used in various industrial and daily life applications. This paper presents a comprehensive vibration analysis and passive control technique for a cantilevered sandwich beam with hourglass lattice truss core fabricated with 3D printing technology. The governing equation of the beam is established by using a homogenized model and Hamilton’s principle, from which the natural frequencies are determined. The theoretical model is verified by the results from the existing literature and the finite element analysis. Frequency response of the sandwich beam measured experimentally further validates the proposed model. Subsequently, a nonlinear energy sink (NES) is proposed for being employed to passively suppress the vibration of the sandwich beam. A parametric study based on the theoretical model confirms the viability of using NES to effectively control the vibration of the sandwich beam. This work provides a solution of using 3D printing technology for sandwich beams with complicated lattice core as well as some guidelines regarding their dynamic analysis.